2020
DOI: 10.1186/s13287-020-1549-6
|View full text |Cite
|
Sign up to set email alerts
|

Management of retinitis pigmentosa by Wharton’s jelly derived mesenchymal stem cells: preliminary clinical results

Abstract: Purpose: The aim of this study is to determine if umbilical cord Wharton's jelly derived mesenchymal stem cells implanted in sub-tenon space have beneficial effects on visual functions in retinitis pigmentosa patients by reactivating the degenerated photoreceptors in dormant phase. Material and methods:This prospective, open-label, phase-3 clinical trial was conducted between April of 2019 and October of 2019 at Ankara University Faculty of Medicine, Department of Ophthalmology. 32 RP patients (34 eyes) were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 72 publications
4
37
0
Order By: Relevance
“…Structural measurements, such as EZW and ORT, and functional measurements such as BCVA, FPDI, and ERG responses can indicate photoreceptor reactivation (Tables 3, 4, and 5). Statistically significant improvements in these parameters show that the paracrine trophic effects of WJ-MSCs still persist during the first year similar to the results at 6th month [46]. Dormant phase reactivation and statistically significant increases were detected in 19 of 34 eyes (55.9%) according to visual field and EZW parameters.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Structural measurements, such as EZW and ORT, and functional measurements such as BCVA, FPDI, and ERG responses can indicate photoreceptor reactivation (Tables 3, 4, and 5). Statistically significant improvements in these parameters show that the paracrine trophic effects of WJ-MSCs still persist during the first year similar to the results at 6th month [46]. Dormant phase reactivation and statistically significant increases were detected in 19 of 34 eyes (55.9%) according to visual field and EZW parameters.…”
Section: Discussionsupporting
confidence: 77%
“…Stem cell-based paracrine trophic therapies can be effective for a large number of patients regardless of the genetic inheritance [ 24 45 ]. For this purpose, stem cell research has increased in recent years, e.g., our previous study with Wharton’s jelly-derived mesenchymal stem cells (WJ-MSCs) in the treatment of RP patients [ 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, even young cells are doomed to perish when introduced into an old organ without a youthful niche [44,45]. Though the recent study demonstrated that sub-tenon WJ-MSCs administration was effective on reactivating the degenerated photoreceptors in dormant phase [13], the long-term effects may be weakened with the gradual aging of WJ-MSCs in vivo, and the senescenceassociated secretory phenotype secreted by senescent WJ-MSCs may even produce adverse effects. Therefore, the idea of providing endogenous or transplanted stem and progenitor cells with better microenvironments is being pursued by many researchers in the eld of regenerative medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Differentiated ESCs and tissue-speci c adult stem cells yield much weaker results than ESCs [22,25,44]. Administration of sub-tenon WJ-MSCs could stop the progression of retinal degeneration and rescue photoreceptors in the dormant phase with the paracrine effects of WJ-MSCs [13]. Interactions between cells involve multi-directional signaling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation